Pengaruh Online Advertising Terhadap Keputusan Pembelian Produk Skintific: Peran Mediasi Trust dan Social Media Engagement (Studi Pada Konsumen Produk Skintific di Kota Malang) - Bela Melissa Arini; Nasarudhin Mas; Choirul Anam (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study aims to analyze the influence of Online Advertising on purchasing decisions for Skintific products by considering the mediating role of Trust and Social Media Engagement. Skintific, as a digital-native skincare brand, actively utilizes digital marketing strategies through various social media platforms such as Instagram, Tiktok, or e-commerce like Shopee to increase consumer appeal, especially in Malang City. This study uses a quantitative approach with the Partial Least Squares Structual Equation Modeling (PLS-SEM) method to test the relationship between variables. The sample was obtained through a purposive sampling technique with 114 respondents who are active consumers of Skintific. The results of this study indicate that Online Advertising has a significant effect on purchasing decisions, both directly and through the mediation of Trust and Social Media Engagement. Theoretically, this study extends the application of the Theory of Reasoned Action (TRA) in explaining the formation of attitudes and subjective norms of consumers towards digital advertising, as well as the Technology Acceptance Model (TAM) which shows how perceived ease and usefulness of digital advertising content affect user engagement. Customer Trust Theory in E-Commerce is used to explain how trust is formed in online transactions, while Relationship Marketing Theory emphasizes the importance of long-term interactions between brands and consumers. The Theory of Planned Behavior (TPB) expands this framework by adding the construct of behavioral control, which explains how consumers' perceptions of ease and barriers contribute to purchasing decisions. Social Influence Theory is used to understand the influence of social norms and online community opinions on purchase intentions, and Uses and Gratifications Theory (UGT) to examine consumer motivations in accessing and interacting with digital content based on information needs, affection, and self-identity. This research provides theoretical contributions in strengthening the relevance of integrating several consumer behavior theories in a digital context.